Immortalization of primary epithelial cells requires first- and second-exon functions of adenovirus type 5 12S. - Quinlan, M P (1992)
Immortalization of primary cells is a multistep process. The adenovirus E1A 12S gene product is a member of the class of oncoproteins that have the ability to establish primary cells as cell lines in culture. It is encoded by two exons. Extensive mutational analysis demonstrates that four regions of the E1A 12S gene, encoded by both exons, are necessary for immortalization of primary epithelial cells. Expression of two regions is necessary to activate quiescent cells into the cell cycle but is unable to extend the life span of these cells in culture and thus cannot immortalize them. These regions are encoded by the first exon. A third first-exon region, for which no function has yet been identified, is also required. These three regions are also required for 12S to cooperate with an activated ras gene to bring about tumorigenic transformation. The fourth region is required to maintain the cells in a proliferative mode, extend their life span in culture, and induce an autocrine growth factor. These functions are encoded by the second exon. The cells immortalized by wild-type 12S and immortalization-competent mutants retain their epithelial morphology and expression of keratin and vimentin intermediate filament proteins.